Tris(acetylacetonato) Iron(III): Recent Developments and Synthetic Applications - Lübken, Dennis; Saxarra, Marius; Kalesse, Markus (Synthesis, 2019)
Tris(acetylacetonato) iron(III) [Fe(acac)3] is an indispensable reagent in synthetic chemistry. Its applications range from hydrogen atom transfer to cross-coupling reactions and to use as a Lewis acid. Consequently, the exceptional utility of Fe(acac)3 has been demonstrated in several total syntheses. This short review summarizes the applications of Fe(acac)3 in methodology and catalysis and highlights its use for the synthesis of medicinally relevant structures and in natural product syntheses.1 Introduction2 Hydrogen Atom Transfer (HAT)3 Oxidations and Radical Transformations4 Synthesis and Use of Alkynes and Allenes5 Cross-Couplings and Cycloisomerizations6 Borylations7 Miscellaneous Reactions8 Conclusions
Keywords: Fe(acac)3; tris(acetylacetonato) iron(III); hydrogen atom transfer; radical transformations; cross-couplings; synthetic chemistry; catalysis